Komunikasi yang Terjadi Dalam Konteks Ruang dan Waktu - Efendi, Erwan; Innayatillah, Innayatillah; Pulungan, Wahyuni; Ritonga, Putri Nadia (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The purpose of this study is to find out about communication that occurs in the context of space and time. In this study the method used was in the form of a qualitative research method, namely by using a literature review and also a literature study. Communication is a message delivery mechanism, in conveying the message, what is there is an expression of language. Communication in the context of space and time means that the information conveyed by the communicator can be adjusted through the context of space or place and time and means where the communication process is carried out or under what conditions. Keywords: Communication, Space and Time